(3egGQGJ GdebGHdGJ GdTNUjI hELQGDgGs - (3OhQdfZ cfOQSdjs; (3ecJHI dHfGf fGTQhfs ((3HjQhJs (3ecJHI dHfGf fGTQhfs, 2001)
(3jbOe gPG GdcJGH CSGdjH YdejI JhVM dc cjajI EOGQI GdebGHdGJ GdTNUjI hcjajI JaSjQ GdEjeGAGJ hdZI GdLSO, cjajI GfJbGA GdeQTM GdeKGdj(B. (3jbhe GdfU GdhGVM hGdQShe GdJhVjMjI HJZWjI cGaI LhGfH GdebGHdI GdTNUjI hJYjjf GdehXajf GdLOOs
(3Ydi GdZdGa (B: (3EYOGO GdbhGFe GdeNJUQI (B- (3GdJfXje (B- (3fUGFM (B- (3GdGSJeGY (B- (3GdEYOGO (B- (3GdCgOGa (B- (3GdJbjje (B- (3JQJjH GdebGYO (B- (3GJNGP GdbQGQGJs
(3jhQc HQSs
1 2 6 10 11 13 14 16
Keywords: (3EOGQI GdCaQGOs; (3GdebGHdGJs; (3GdfLGM GdTNUjs